Case series, contemporary review and imaging guided diagnostic and management approach of congenital pericardial defects. Issue 1 (8th January 2020) - Khayata, Mohamed; Alkharabsheh, Saqer; Shah, Nishant P; Verma, Beni Rai; Gentry, James L; Summers, Mathew; Xu, Bo; Asher, Craig; Klein, Allan L
Abstract : Objective: Congenital pericardial defect (CPD) is a rare entity with an estimated frequency of 0.01%–0.04%. The recognition of this anomaly is important since it can be associated with serious complications. The aim of this study and review was to describe clinical and imaging features that help in establishing the diagnosis of this condition. Methods: We retrospectively reviewed all adult patients at the Cleveland Clinic Health System with the diagnosis of CPD between the years 2000 and 2015. Baseline clinical characteristics, clinical manifestations, ECG, transthoracic echocardiography (TTE), cardiac CT and cardiac magnetic resonance (CMR) images were reviewed. Results: Eight patients were included in the study. Sixty-three percent of patients were males with mean age at diagnosis of 48 years, 63% had a partial pericardial defect on the left side and right ventricular (RV) dilation on TTE. Three patients had CMR. Levocardia was present in all CMRs. One patient had greater than 60° clockwise rotation and none of the CMRs showed ballooning of the left ventricular apex. One patient required surgical pericardioplasty. The remaining seven patients had a median follow-up of 17.3 months (5–144.9 months) and all remained asymptomatic. Conclusion: CPDs are more likely to be partial on the left side and patients often have RV dilation on the TTE and levocardia on CMR. Most patients remain stable and do not require surgical intervention. TTE and CMR play an important role in making the diagnosis of this anomaly.